Empathetic Space on Screen - D’Adamo, Amedeo (Springer, 2018)
In cinema and television empathetic settings stand out above all others.1 Think of the now iconic gooey dripping tunnels that Ripley stumbles through in Aliens (1986; see Fig. 1.2), or the delightful melancholic wonderland of Paris so winningly animated by the winsome protagonist of Amelie (2001) (Fig. 1.1). Other examples come to mind—the sewers of The Third Man (1949), or Norman’s bird-decorated parlor in Psycho (1960), or the dark Gotham of certain Batman movies, or certain moments in Homeland (2011–), Mad Men and other television shows. Because we lack a clear account of the power of setting and space we are reduced to describing such narratives as ‘atmospheric’, ‘emotionally moody,’ or perhaps somehow illustrating a ‘romantic aesthetic’, but can we define them more concretely? Why do these settings stand out so memorably in narrative history when so many others, however spectacular and breathtaking and adrenalynic, start to fade from our view as the end-credits roll up? Could we dissect their craft and story techniques, show an underlying unity and even illustrate how and why they differ from other uses of narrative space? In short, what makes these particular spaces so powerful and iconic?
Constructing Powerful Place and Setting